2014
DOI: 10.3346/jkms.2014.29.10.1385
|View full text |Cite
|
Sign up to set email alerts
|

Association between Adipokines and Coronary Artery Lesions in Children with Kawasaki Disease

Abstract: Body fat is an important source of adipokine, which is associated with energy balance and inflammatory and immune responses. However, the role of adipokines in coronary artery complications in Kawasaki disease (KD) has not yet been fully explained. We investigated whether serum adipokine level can be a useful marker for patients with KD who are at higher risk of developing coronary artery lesion (CAL). We measured adipokine levels and other inflammatory parameters in 40 patients with KD, 32 febrile controls, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 24 publications
(24 reference statements)
1
14
0
Order By: Relevance
“…The present meta-analysis revealed that the levels of resistin were significantly higher in the KD group compared with those in the DC group (MD=21.27, 95% CI=14.24-28.29, P<0.001; Table II; Fig. 2B) (18,19,21). However, no statistically significant differences in adiponectin levels were identified between the KD group and the DC group (MD=-5.49, 95% CI=-11.28-0.31, P=0.06; Fig.…”
Section: Resultsmentioning
confidence: 65%
See 4 more Smart Citations
“…The present meta-analysis revealed that the levels of resistin were significantly higher in the KD group compared with those in the DC group (MD=21.27, 95% CI=14.24-28.29, P<0.001; Table II; Fig. 2B) (18,19,21). However, no statistically significant differences in adiponectin levels were identified between the KD group and the DC group (MD=-5.49, 95% CI=-11.28-0.31, P=0.06; Fig.…”
Section: Resultsmentioning
confidence: 65%
“…However, no statistically significant differences in adiponectin levels were identified between the KD group and the DC group (MD=-5.49, 95% CI=-11.28-0.31, P=0.06; Fig. 2C and D) (17,(20)(21)(22)24,25).…”
Section: Resultsmentioning
confidence: 94%
See 3 more Smart Citations